1994
DOI: 10.1177/074355489493003
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-Related Items for Developing an AIDS Questionnaire for Children and Adolescents

Abstract: This study presents a pool of AIDS-related items that researchers and clinicians could use to develop self-report AIDS questionnaires for children and adolescents. A total of 352AIDS-related itemsfrom 18AIDSsurvey studies involving children and adolescents, ranging in age from 10 to 21 years, were submitted to content analysis. Unique items with 85% agreement among raters, and items with the higher percentage of agreement (85% or above) among repeated items, were selected. On the basis of these criteria, 164 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
1
16
1
1
Order By: Relevance
“…Furthermore, as the HIV/AIDS epidemic is a global concern, a comprehensive measure of HIV/AIDS awareness should also enable cross-cultural comparisons. While several studies have investigated HIV/AIDS knowledge (Lewis, Malow, & Ireland, 1997;Li et al, 2004;Odusanya & Alakija, 2004), or attitudes, (Bruce & Reid, 1998;Bruce & Walker, 2001), there has been little research using multidimensional measures of HIV/AIDS awareness (Paniagua et al, 1994), and we have found no existing multidimensional HIV/AIDS questionnaires that enable cross-cultural comparisons in different languages. Therefore, this paper assessed the reliability and validity of an HIV/AIDS questionnaire that measures fours dimensions of HIV/AIDS awareness-factual knowledge, prejudice, personal risk, and misconceptions about HIV transmission, and will enable cross-cultural research.…”
Section: Hiv/aids Prevention In Children and Youthmentioning
confidence: 99%
“…Furthermore, as the HIV/AIDS epidemic is a global concern, a comprehensive measure of HIV/AIDS awareness should also enable cross-cultural comparisons. While several studies have investigated HIV/AIDS knowledge (Lewis, Malow, & Ireland, 1997;Li et al, 2004;Odusanya & Alakija, 2004), or attitudes, (Bruce & Reid, 1998;Bruce & Walker, 2001), there has been little research using multidimensional measures of HIV/AIDS awareness (Paniagua et al, 1994), and we have found no existing multidimensional HIV/AIDS questionnaires that enable cross-cultural comparisons in different languages. Therefore, this paper assessed the reliability and validity of an HIV/AIDS questionnaire that measures fours dimensions of HIV/AIDS awareness-factual knowledge, prejudice, personal risk, and misconceptions about HIV transmission, and will enable cross-cultural research.…”
Section: Hiv/aids Prevention In Children and Youthmentioning
confidence: 99%
“…Psychiatric diagnoses were made using the DSM-IW (American Psychiatric Association, 1987). Paniagua et al (1994) identified 352 HIVIAIDS-related items used in prior studies with adolescents representing healthy adolescents, juvenile delinquents, pregnant adolescents, runaways, and dropouts. Psychiatrically hospitalized adolescents were not included.…”
Section: Methods Sanrplementioning
confidence: 99%
“…transmission, these are not included in the scale so as to only measure one dimension of HIV/AIDS transmission information-misconceptions. These questions were chosen from the hundreds of AIDS-related questions for adolescents and children that have been tested for content validity (Paniagua et al 1994). In addition, test-retest reliability (.84 at time one and .86 at time two, [Sittig 1996]) showed that young children do not have a problem giving reliable answers to the questions concerning the transmission of the AIDS virus (Sly, Eberstein, Quadagno, Kistner, Hummer and Hussey 1992).…”
Section: Heterosexism and Aids Attitudes 325mentioning
confidence: 99%